The Drought disaster mitigation efforts based on water catchment potential in Samosir Island - Rumahorbo, Novita Sari; Slamet, Bejo; Anggraini, Novita (Global Forest Journal, 2025)
Samosir Island is part of the upstream area of the Asahan Toba watershed. Samosir Island is often hit by drought, making getting water from rainwater and groundwater difficult. One critical information needed for drought mitigation is the spatial distribution of the potential of water catchment areas. This study analyses the spatial distribution of the potential of water catchment areas and mitigation efforts. The parameters are soil type, rainfall, land use, and slope. Spatial analysis was conducted using a Geographic Information System (GIS) with scoring and overlay techniques. The results showed that the potential of water catchment areas in Samosir Island was categorized into four classes: natural normal covering of 2.77 hectares (0.004%), starting to be critical of 8,808.001 hectares (13.647%), somewhat critical of 48,000.327 hectares (74.369%), and critical of 7,732.647 hectares (11.980%). Drought mitigation in Samosir Island related to the distribution of the potential of water catchment areas is by maintaining vegetation, planting trees and understoreys, repairing terrace boundaries, building Rainwater Harvesting Installations, and creating biopores.